Sociological Effects of Artificial Intelligence on Theological Students in Selected Seminaries of The Church of Nigeria (Anglican Communion) - Ogunbiyi , David Oluwabukunmi; Oyebanji , Israel Temitope (Corpus Intellectual, 2025)
Artificial intelligence, a computer science field, can revolutionise education by enabling machines to perceive their environment and use learning to achieve goals. However, it poses threats to teachers’ job security, dehumanised learning experiences, and increased dependency on technology. Overreliance on AI can limit critical thinking and cognitive abilities, making students increasingly dependent on machines. The study investigates the effect of artificial intelligence on theological education, particularly among Anglican postulants in Church of Nigeria seminaries. The research involved 82 participants from three major geopolitical zones in Nigeria, including 27 lecturers and 55 students from Immanuel College of Theology & Christian Education and Archbishop Vining College of Theology. The results showed that in Anglican seminaries of the Church of Nigeria (Anglican Communion), artificial intelligence can improve education through adaptive learning platforms, automated grading systems, virtual teaching assistants, speech recognition, behavioural analytics, assignment and research compilations, and realtime student behaviour monitoring. Artificial intelligence can also provide immediate feedback. However, concerns about data privacy, algorithmic biases, and overreliance on technology can hinder the social, spiritual, emotional, and psychological developments of the postulants in Anglican seminaries. The study recommended that the Church of Nigeria (Anglican Communion), through its recently established theological accreditation and regulatory board, establish a subcommittee to evaluate the effects of artificial intelligence (AI) on the spiritual, psychological and mental development of Anglican postulants in Nigeria. This subcommittee should create policy documents on AI, take ethical and responsible measures in its implementation, and raise awareness of the effects of AI in society, parishes, and educational institutions.